Strategic Design for Optimizing Productive Assets in Banking: A Case Study of PT Bank ICBC Indonesia - Sandra Dewinta Nugroho; Andrianto Widjaja (Eastasouth Institute, 2026)
The optimization of productive assets is an important factor in improving bank performance and financial stability. This study aims to identify internal and external factors influencing the optimization of productive assets at PT Bank ICBC Indonesia and to formulate strategic recommendations to enhance the Bank’s performance. The research employs a case study approach using strategic management analysis through the integration of the IFE, EFE, IE, TOWS, and QSPM matrix. Data were collected through interviews with internal informants and document study of the company. The results show that the IFE matrix score is 2.84 and the EFE matrix score is 3.32, which places the Bank’s position in the IE matrix falls within the grow and build category, and reflecting strong potential for expansion through growth strategies. Strategy formulation through TOWS integrated with IE matrix generated several alternative strategies, which were further evaluated using QSPM to determine strategic priorities. The results of the QSPM analysis indicate that the top priotity strategies are strengthening corporate financing for Chinese companies investing in Indonesia as well as Indonesian companies with business linkages to China, and developing RMB-based financial services. Both strategies are considered the most effective in optimizing productive assets while strengthening the Bank’s competitiveness.